Pd(OAc)2-Catalyzed Desulfinative Cross-Coupling of Sodium Sulfinates with β-Bromostyrenes: Synthesis of Tamoxifen - Chang, Meng-Yang; Cheng, Yu- Chieh; Sun, Pei- Pei (Synthesis, 2017)
A Pd(OAc)2-catalyzed desulfinative cross-coupling of (Z)-β-halostyrenes with sodium sulfinates in the presence of PPh3 and Na2CO3 at reflux in good yields is reported. The stereocontrolled cross-coupling process provides a series of sulfonylmethyl (Z)-stilbenes. A synthesis of tamoxifen was studied.
Keywords: desulfinative cross coupling; halostyrenes; sodium sulfinates; stilbenes; tamoxifen